The hidden language skill: oral inferential comprehension in children with developmental language disorder - Dawes, Emily Catherine (Curtin University, 2017)
Children with developmental language disorder (DLD) experience significant difficulty with inferential comprehension, a skill which is essential for effective communication and reading comprehension. The first study created a profile of the language and cognitive skills which significantly contribute to oral inferential comprehension in 5 to 6 year old children with DLD. The second study was a randomised controlled trial of a novel inferential comprehension intervention which was effective at improving the skill in this population.